Emergency physicians as human billboards for injury prevention: a randomized controlled trial. Issue 4 (15th September 2016) - Sullivan, Emily; Fuller, Daniel; Paterson, Quinten S.; Huffman, Shelby; Challa, Satyadeva; Woods, Rob
ABSTRACT: Objectives: The objective of this study was to evaluate the impact of a novel injury prevention intervention designed to prompt patients to initiate an injury prevention discussion with the ED physician, thus enabling injury prevention counselling and increasing bicycle helmet use among patients. Methods: A repeated measures 2 x 3 randomized controlled trial design was used. Fourteen emergency physicians were observed for two shifts each between June and August 2013. Each pair of shifts was randomized to either an injury prevention shift, during which the emergency physician would wear a customized scrub top, or a control shift. The outcomes of interest were physician time spent discussing injury prevention, current helmet use, and self-reported change in helmet use rates at one year. Logistic regression analyses were used to examine the impact of the intervention. Results: The average time spent on injury prevention for all patients was 3.3 seconds. For those patients who actually received counselling, the average time spent was 17.0 seconds. The scrub top intervention did not significantly change helmet use rates at one year. The intervention also had no significant impact on patient decisions to change or reinforcement of helmet use. Conclusions: Our study showed that the intervention did not increase physician injury prevention counselling or self-reported bicycle helmet use rates among patients. Given the study limitations, replication and extension of the intervention is warranted. RÉSUMÉ: Objectif: L'étude décrite ici visait à évaluer la portée d'une nouvelle intervention de prévention des blessures, conçue pour inciter les patients à amorcer une discussion sur la prévention avec le médecin d'urgence, ce qui donnait l'occasion de donner des conseils sur la prévention des blessures et de favoriser le port du casque de bicyclette chez les patients. Méthode: Il s'agit d'un essai comparatif avec répartition au hasard, de type 2x3, et avec reprise de mesures. Quatorze médecins d'urgence ont fait l'objet d'observation durant deux périodes de travail chacun, entre juin et août 2013. La répartition de chaque doublet vers la période de prévention des blessures au cours de laquelle le médecin d'urgence portait une blouse de chirurgie adaptée à l'intervention ou vers la période de travail témoin a été faite au hasard. Les résultats d'intérêt étaient le temps passé par le médecin à parler de la prévention des blessures, les habitudes du port du casque au moment de l'entrevue et les changements de taux de port autodéclaré du casque au bout de un an. Enfin, la portée de l'intervention a été examinée à l'aide d'analyses de régression logistique. Résultats: Le temps moyen passé à parler de la prévention des blessures dans l'ensemble des patients était de 3, 3 secondes, et celui passé chez ceux qui ont bel et bien reçu des conseils s'élevait à 17, 0 secondes. L'intervention du port de la blouse de chirurgie a eu peu d'incidence sur le taux de port du casque au bout de un an et il en a été de même pour la décision des patients de changer ou de renforcer leur habitude du port du casque. Conclusions: L'étude a démontré que l'intervention n'avait pas eu pour effet d'accroître le temps passé par les médecins à donner des conseils sur la prévention des blessures ou d'augmenter le taux de port autodéclaré du casque de bicyclette chez les patients. Compte tenu des limites de l'étude, il est justifié de répéter ou de prolonger l'intervention.